Pemanfaatan Limbah Jagung Untuk Dijadikan Bahan Kemasan Ramah Lingkungan - Aziz, Adib Abdul; Aulia, Salsa; Paiz, Moc Najmi; Noer, Shela Mazidah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The food industry is experiencing an increase so that the need for food packaging is high. Food packaging usually uses plastic or disposable packaging. Plastic packaging has different permeability properties, therefore the right plastic packaging is needed to prevent damage. Indonesia, especially East Java, has an abundant corn harvest, corn waste is often considered just waste without economic value, causing serious environmental problems, such as burning waste. This research was carried out with the aim of utilizing corn husk and cob waste so that it can add economic value to farmers by being used as material for making environmentally friendly containers. This research is a qualitative and quantitative research. This combined method is called a combined research methodology. The results of observational research, interviews and questionnaires conducted by research focused on the use of corn husk and corn cob waste. The results of the researcher's observations saw that there was a lot of corn being sold in the market and the researcher also saw that the corn husks were scattered and piled up without any utilization. Meanwhile, for corn cob waste, the researcher did not see any such waste in the market, but the researcher looked for information that there was a lot of corn cob waste when he only took the seeds. From the results of this research, it can be concluded that corn waste has great potential to be used as environmentally friendly packaging material and adds economic value for corn farmers and traders. The food industry sector has a high need for packaging, but the plastic packaging that is generally used can damage the environment. Utilizing corn waste as packaging material can reduce the negative environmental impacts of using plastic packaging and provide additional economic benefits for farmers.